17. ASSESS THE KNOWLEDGE OF MEDICAL STAFF ON THE MEDICAL WASTE MANAGEMENT AT CANCER INSTITUTE, 108 MILITARY CENTRAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objects: Evaluate medical staff’s knowledge of medical waste management to take measures to improve awareness and practice of medical staff in the Cancer Institute, 108 Central Military Hospital.Subject and methods: Cross-sectional descriptive study used questionnaires to survey the knowledge and practice of health workers on the management of medical waste.Results: The percentage of medical staff have proper knowledge about the types of medical waste is very low, the doctor is 15.6%; nursing is 34.6%; correct knowledge about infectious waste is 56.3% of the doctors; nursing is 82.7%; engineer 57.2% and hygienic staff is 42.8%. The number of doctors understood the participants classified medical waste is 43.8%; nursing is 80.7%. Where the classification of medical solid waste, the percentage of correct understanding of doctors is 56.3%; nursing is 82.7%; engineer is 28.6% and hygienic staff is 42.9%. Understanding the object at risk due to unsafe medical waste is 78.2% of the doctors; nursing is 94.2%. Right understanding of process management of sharps injuries is 40.6% of the doctors and nursing is 71.2%. The knowledge about infection prevention measures of doctors is 78.2% and nursing is 94.2%. Knowledge of the process of handling injuries caused by sharp objects, the doctor has the right understanding is 68.7% and nursing is 78.8%.
Keywords: Medical solid waste; manage; knowledge